Towards a contextual approach: Audiences, television and 'offensive' humour. (April 2020) - Graefer, Anne; Das, Ranjana
The fine line between humour and offence has long been of interest for scholars and media outlets alike. While some argue for an avoidance of offence at all costs, others defend the 'right to offend' as an essential part of humour. By bringing critical sociological studies in humour into dialogue with feminist writings on affect and the politics of emotion, this article argues for a more nuanced and contextualised understanding of offensive humour. Based on empirical data from an audience study about offensive television content in Britain and Germany, we consider what exactly people do with humorous content they find offensive, not what it does 'in general'. Such a contextualised approach illustrates the ethical and transformative potential of so-called negative affect. Thus, rather than perceiving offence as an 'ugly' feeling with merely negative consequences for society, this article contends that the avoidance of offence can also operate as a strategy for evading responsibility and action, thereby hindering social change.